The potential of behavioural activation for the treatment of chronic pain: An exploratory review - Mazzucchelli, Trevor; Da Silva, M. (Wiley-Blackwell Publishing Ltd., 2016)
Background: A substantial proportion of the population have a persistent pain condition. In addition to considerable personal suffering, these conditions have a massive economic cost at a society level in terms of health expenditure and lost productivity. To address this immense public health problem, treatment approaches are needed that are based on scientifically supported theories and that are easy to disseminate and scalable. Method: An exploratory qualitative review of literature concerning the operant model of chronic pain, related psychological interventions, and a synopsis of existing intervention studies with a behavioural activation (BA) approach was undertaken. Results: Current treatments for chronic pain are multimodal, however early research showed promising results for operant-based behavioural intervention alone. Although originally developed for depression, BA is a good theoretical match for operant conceptions of chronic pain. Further, because of its relative simplicity, BA is appealing in terms of its potential ease of dissemination. Two case studies have used BA for individuals suffering from fibromyalgia and produced promising treatment outcomes. Conclusions: Further research investigating the efficacy of BA for chronic pain is justified. Such work should begin with more single subject experimental designs to explore how BA might be best applied and the generalisability of the approach.